GEOGRAPHICAL DIMENSION OF MSM SOCIALIZATION SPACES IN GUATEMALA CITY AND ITS RELATIONSHIP WITH TOURISM - Sánchez-Crispín, Álvaro (2016)
This paper examines the issue of the territorial arrangement of MSM (men who have sex with men) socialization spaces in Guatemala City and its relationship with tourism. First, we analyze some of the main concepts associated with the explanation of how such places have managed to occupy certain areas within the urban area. Then, we present an overview of Guatemala City as the central place of the country providing services to nationals and foreigners alike. The main research results are given in the last part of the paper, pinpointing at the territorial expression of the places studied. One important finding is that, regardless of its demographic volume, Guatemala City offers a limited number of homoerotic locations. These have a clearly identifiable hinterland, drawn along the southern areas of the country, and including places in neighboring countries such as El Salvador.